2021
DOI: 10.2478/abm-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature stable loop-mediated isothermal amplification (LAMP) reagents to detect leptospiral DNA

Abstract: Background Loop-mediated isothermal amplification (LAMP) is one of the most promising tools for rapidly detecting Leptospira spp. However, LAMP is hampered by cold storage to maintain the enzymatic activity of Bst DNA polymerase. Objective To overcome the drawback of cold storage requirement for LAMP reagents we modified the reagents by adding sucrose as stabilizer. We then sought to determine the stability at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Other studies reported stability of up to 15 days at 25 or 37 °C 49 and up to 45 days at room temperature. 50 For the RTs, both CQMED HIV -RT and CQMED GO -RT maintained their activity, with little (room temperature) or no loss of function (4 °C) for up to 60 days of adverse storage, the longest tested condition.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies reported stability of up to 15 days at 25 or 37 °C 49 and up to 45 days at room temperature. 50 For the RTs, both CQMED HIV -RT and CQMED GO -RT maintained their activity, with little (room temperature) or no loss of function (4 °C) for up to 60 days of adverse storage, the longest tested condition.…”
Section: Discussionmentioning
confidence: 89%
“…A series of experiments were conducted to assess the quality of the enzymes produced in-house and to determine their effectiveness, even under adverse storage conditions, based on the guidelines established in EP25-A (Evaluation of Stability of In vitro Diagnostic Reagents) 47 with modifications, and results from previous works. [48][49][50] The activities of the CQMED enzymes, Bst-LF and HIV-RT, were evaluated after several weeks of storage in non-ideal temperatures, compared to the enzymes kept at the recommended storage condition of −20 °C. Figure 3(A) demonstrates that average LAMP Ct (Cycle threshold) values ranging from 16 to 20 were observed for CQMED Bst-LF across the tested time points.…”
Section: Enzymes Are Stable Over Time At Different Storage Temperatur...mentioning
confidence: 99%
“…Therefore, employing this detection kit would be difficult at a point of care, especially in rural areas where the cold chain transportation and electricity could not be accessed. Several studies have attempted to prolong the stability of the reaction components at ambient temperature 48 50 . In this study, we have overcome this issue by adding specific stabilizers to preserve the structure of the biological molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To design the LAMP primers, OptiGene LAMP Designer software ( http://www.optigene.co.uk/lamp-designer/ ) was used. The LAMP primer set consists of two outermost primers (F3 and B3), two inner primers (FIP and BIP), and two loop primers (LF and LB) ( Lee et al, 2021 ). The primer sequences are listed in Table 1 and their respective mapped regions are shown in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of human infections have been attributed to rats and other rodent species, which are known to be a permanent carrier of Leptospira spp. Previous outbreaks of leptospirosis have been linked with intense periods of high rainfall, which facilitates the spreading of leptospires shedding in the urban environment ( Lee et al, 2021 ). In humans, a wide range of non-specific symptoms such as high fever, headache, muscle ache, and vomiting may appear, and these are often mistaken for other diseases.…”
Section: Introductionmentioning
confidence: 99%